Characterization of fractionated dissolved organic matter in industrial estate wastewater using spectrofluorometry and pyrolysis GC/MS analysis - Charongpun Musikavong (Chulalongkorn University, 2014)
Thesis (Ph.D.)--Chulalongkorn University, 2006